Highly photostable fluorescent probes for multi-color and super-resolution imaging of cell organelles - Byun Gyuwon; Kim Soh-Youn; Choi Min-Woo; Yang, Jin Kyoung; Kwon, Ji Eon; Kim Sehoon; Park Soo Young (Elsevier BV, 2022)
High-performance microscopy with organelle-targeting fluorescent probes has been an indispensable bioimaging tool for cell biology. Confocal or super-resolution imaging often requires highly magnified and/or longitudinal scanning conditions, necessitating the advent of photostable fluorophores. Herein, we report novel organelle targeting fluorescent probes derived from a highly photostable fluorophoric skeleton, i.e., 1,5-naphthyridine2,6-dione (NTD). With organelle-specific derivatization and pi-conjugation extention, we developed NTD-based molecular probes with blue-to-red fluorescence tunability and intracellular organelle selectivity for staining, as well as minimal cytotoxicity, which allowed us to demonstrate intracellular differentiation of lysosomes and mitochondria by multi-color confocal imaging. Under the condition of longitudinal microscopic examination, these new probes showed excellent photostability of fluorescent signals as opposed to the rapid photobleaching of commercial trackers. By virtue of these beneficial properties, the NTD-based probes were successfully applied to super-resolution cell imaging by enduring the high-power illumination conditions of sub-diffraction microscopic techniques including stimulated emission depletion (STED) and structured illumination microscopy (SIM).